Peaceableness as a Weapon in Wars of Swedology - Östlund, David (Scandinavistica Vilnensis, 2019)
This article brings forward a set of examples from the “Swedological” literature that had its golden era circa 1930–1980 – i.e. non-Swedish interpretations of Swedish society (or features of it), done in order to fight ideological wars on non-Swedish soil, using Sweden as a case in point. The theme of Sweden as a peaceful nation, both in its internal developments and in its role in the world, was a crucial feature of the genre from the outset. It has been possible to interpret Sweden’s neutrality policies (including heavy production and exports of arms) in different ways. This has also been the case with Swedish attempts to take responsibility in the world, showing global conscience (e.g. through criticism against international bullies or through foreign aid). The theme of peaceableness has, over the decades, been a tool in fights between “Swedophiles” and “Swedoclasts”, both sides applying a certain “logic of debunkery” in their mutual attempts to disclose the opposite camp’s depictions as myths.
Keywords: Images of Sweden; peace; neutrality; welfare state; industrial relations; global conscience